Peran Teknologi Digital Dalam Pemilihan Umum Demi Mewujudkan Pemilihan Umum Berintegritas - Yuli Purnama, Taufiq; Kusuma Dewi, Retno Catur; Haryani, Anik Tri (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
The purpose of this research is to provide an increase in the use of technology, especially digital technology, in the implementation of elections in a democratic country like Indonesia. The 2024 General Election faces various challenges that arise, so there is a need for digitalisation in democracy that will simplify the process of implementing General Elections in the future. The utilisation of digital technology, especially social media, is key in the implementation of future General Elections to simplify the election process as well as a channel of communication and information to the public or voters. This research uses normative legal research methods conducted by examining library materials with primary legal sources in the form of Law Number 7 of 2017 concerning General Elections, Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions, General Election Commission Regulation Number 15 of 2023 concerning General Election Campaigns, and secondary legal sources in the form of books, journals and other literature. As a result of the research, it is known that the application of digital technology is expected to increase voter participation and the quality of democracy in Indonesia, reduce fraud, create more transparent, accountable, sustainable elections, and reduce problems that arise during General Elections. On the other hand, improving the skills of election organisers is also needed to improve professionalism and prevent mistakes.